Efficient Tapping Systems of Hevea brasiliensis Clones with Active Metabolism IRCA 18, IRCA 111, IRCA 130, PB 235 and PB 260 in Côte d’Ivoire - S. Obouayeba; M. Diarrassouba; E. F. Soumahin; J. L. Essehi; M. K. Okoma; C. B. Y. Adou; A. P. Obouayeba (Cutting-edge Research in Agricultural Sciences Vol. 6, 2021)
To take into account the sensitivity of metabolically active clones, which negatively affects their rubber productivity, a study determining suitable tapping systems for clones (IRCA18, IRCA 111, IRCA 130, PB 235 and PB 260) of this metabolic class, the availability of tappers and socio-economic conditions, was conducted in the southwest of Côte d’Ivoire. Six tapping systems S/2 d2 6d/7 no stimulation; S/2 d3 6d/7 ET2.5% Pa1 (1) 4/y; S/2 d4 6d/7 ET2.5% Pa1 (1) 4/y; S/2 d4 6d/7 ET2.5% Pa1 (1) 8/y; S/2 d5 6d/7 ET2.5% Pa1 (1) 8/y; S/2 d6 6d/7 ET2.5% Pa1 (1) 10/y tested in a randomized full block device with 4 replicates. Parameters measured were rubber yield, radial vegetative growth and Tapping Panel Dryness (TPD) sensitivity. The results show that these clones are very productive (2300 ± 310 kg.ha-1). The average TPD rate (8.5%) is relatively low compared to the reference rate of clones with active metabolism suitable for tapping systems from clones of this class because they are respectively consumers of bark (short latex harvest time) and increase the TPD. On the other hand, the tapping systems S/2 d3 6d/7 ET2.5% Pa1 (1) 4/y; S/2 d4 6d/7 ET2.5% Pa1 (1) 4/y; S/2 d5 6d/7 ET2.5% Pa1 (1) 8/y and S/2 d6 6d/7 ET2.5% Pa1 (1) 10/y are best suited to tapping systems from metabolic clones active as they yield good rubber productivity while maintaining good vegetative growth with a low TPD. They also allow efficient management of the availability of tapper labor.